THE EFFECTIVENESS OF ASEAN WAY IN SOLVING SOUTH CHINA SEA DISPUTES - Epril Setiawan (HI 15 UMY 439, 2015)
*439 The South China Sea is a region which has abundance of both renewable and non-renewable natural resources. Besides, a very strategic geographical location and contain a high economic value increase significant value of this region. The South China Sea is an area that has the most seeds of conflict in Asia-Pacific regions. This undergraduate thesis elaborates the effectiveness of ASEAN Ways in solving disputes and the South China Sea disputes. The writer will focus on creating the mechanism to solve the South China Sea disputes using ASEAN Way as the main way in doing diplomacy, both by informal or formal meeting. In fact, ASEAN has conducted numerous meetings and negotiations as the implementation of the ASEAN Way. The effort is expected to resolve existing disputes, or even just to reduce conflict tensions over the South China Sea by the creation of a declaration and also through negotiations. ASEAN has addressed the issue of the South China Sea in Senior Official Meetings, ASEAN Ministerial Meetings, and the ASEAN Regional Forum. Informal meetings have also been pursued through workshops on Managing Potential Conflicts in the South China Sea held by the initiative of Indonesia since 1990. It is very interesting to know the effectiveness of ASEAN Way in solving the South China Sea disputes. Keyword: dispute, ASEAN, ASEAN Way, and the South China Sea